The Viability of Implementation of the Job Guarantee Program in Brazil - Brandão, Vinicius; Feijó, Carmem (Brazilian Keynesian Review, 2025)
The persistence of elevated unemployment rates globally, particularly in Brazil during the latter half of the 2010s, underscores the necessity for a more comprehensive examination of economic policies aimed at fostering employment. Furthermore, in this context, work conditions are deteriorating with the proliferation of digital platform-based employment and the emergence of part-time work. This is occurring concurrently with policies designed to reduce labor costs and stimulate private investment. In this way, we present the fundamental bases of the Job Guarantee Program, conceived by Hyman Minsky, which places the state as the employer of last resort to eliminate involuntary unemployment. Furthermore, it is necessary to analyze the feasibility of implementing a job guarantee program in Brazil and how it would be integrated into the existing labor market structure.